MECHANICAL STRENGTH OF MATERIALS APPLIED IN SOIL STABILIZATION: A LITERATURE REVIEW - Maria Alves de Oliveira, Ana (Journal of Interdisciplinary Debates, 2023)
Road works and other civil works involve large amounts of materials and earth movements that could be minimized with the best use of material from the construction site itself, through the process of improving the soil obtained from the union with materials able to add resistance. This is because, when the soil is loaded, it tends to deform and this disturbance alters the load flow of the structure, modifying the effort value achieved in the project. For these reasons, the objective of this work was to analyze the mechanical resistance of materials applied in the improvement and stabilization of soils. Therefore, knowing the lineage of this theme, this study was developed with the intention of identifying, in the literature, consistent treatments that favor the inheritance of soil resistance. This is an integrative review carried out on scientific data sources: Scientific Electronic Online Library (SciELO) and Google Scholar. Searches for studies were carried out from August to December 2022. The descriptors selected to search for data were: road works, soil improvement and soil stabilization. The inclusion criteria for the selection of scientific articles were: articles published from 2001 to 2017, in Portuguese; monographs, theses, dissertations, available and complete articles. Exclusion criteria were: publications of repeated articles in databases.To implement soil stabilization, many issues need to be persistent, in the study one of them was that the cement presents stable performance in soil stabilization, reaching SSI rates above 80% for base according to DNIT. As well as the alternative materials, they present the values for application in base and subgrade, with the superior capacity of 2% of ISC for the subgrade when applied with sludge ash and lime reaching the guidelines for use in the base.